Neuropathology Review - Prayson, Richard A. (Humana Press, 2001)
As scientific research expands the scope of neuropathology, the amount of information that both student and practicing pathologists must assimilate and master can be challenging, and at times even daunting. In Neuropathology Review, Richard A. Prayson, md, thoroughly summarizes in outline form the essential elements of the neuropathology curriculum for all those seeking a concise up-to-date overview of the subject. Topics range from basic information on the spectrum of neurologic-related disease to pertinent pictorial examples of many neuropathologic conditions. For each topic there are self-assessment tests based on both textual and pictorial material, along with sample answers and explanations designed to aid comprehension and understanding. Concise yet comprehensive, Neuropathology Review provides an effective and easy-to-use refresher course for those working pathologists wishing to update their skills, as well as for students and residents preparing to take board exams in neuropathology